Infrastructure, Incentives, and Institutions - Ashraf, Nava; Glaeser, Edward L.; Ponzetto, Giacomo A. M. (American Economic Review, 2016)
Expensive infrastructure is ineffective if it doesn't travel the last mile. In nineteenth-century New York and modern Africa, disease has spread when urbanites chose not to use newly built sanitation infrastructure to save money. Either subsidies or Pigouvian fines can internalize the externalities that occur when people don't use sanitation infrastructure, but with weak institutions subsidies generate waste and fines lead to extortion. Our model illustrates the complementarity between infrastructure and institutions and shows how institutional weaknesses determine whether fines, subsidies, both or neither are optimal. Contrary to Becker (1968), the optimal fine is often mild to reduce extortion.